2018
DOI: 10.1016/j.btre.2017.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of two crude oil-degrading fungi strains from Rumaila oil field, Iraq

Abstract: HighlightsThe ability of indigenous fungi in degradation of crude oil was examined.Two strains exhibited a cell surface hydrophobicity higher than 70%.The two strains RMA1 and RMA2 reduced surface tension in MSM containing 1% crude oil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 25 publications
7
54
0
1
Order By: Relevance
“…It was also reported that two crude oil‐degrading fungi isolated from the Rumaila oilfield, Penicillium sp. RMA1 and RMA2 could grow in media containing crude oil and further degrade (57% and 55%, respectively), illustrating that those two fungi could metabolize crude oil efficiently (Al‐Hawash et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…It was also reported that two crude oil‐degrading fungi isolated from the Rumaila oilfield, Penicillium sp. RMA1 and RMA2 could grow in media containing crude oil and further degrade (57% and 55%, respectively), illustrating that those two fungi could metabolize crude oil efficiently (Al‐Hawash et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, in the present study, the fungal community was rich of Aspergillus and Penicillium. Aspergillus and Penicillium strains have been already isolated in several polluted samples ( Chaıneau et al, 1999 ; Da Silva et al, 2003 ; Zafra et al, 2014 ; Al-Hawash et al, 2018 ). Data on soil isolation of Aspergillus niger ( Chaıneau et al, 1999 ) , Aspergillus fumigatus ( Chaıneau et al, 1999 ; Zafra et al, 2014 ), Aspergillus terreus ( Da Silva et al, 2003 ), Aspergillus flavus, Aspergillus niger, Aspergillus nomius ( Zafra et al, 2014 ), Aspergillus sydowii ( Tian et al, 2016 ), Aspergillus versicolor ( Šimonovièová et al, 2017 ) have been reported although few information deals with the here-detected species of Aspergillus (i.e., A. creber, A. jensenii, A. protuberus ).…”
Section: Discussionmentioning
confidence: 99%
“…RMA1 and RMA2 was reported to reduce the surface tension. According to the published reports, there is a direct relationship between biodegradation ability of fungi and a reduced surface tension . Therefore, Daedaleopsis sp.…”
Section: Discussionmentioning
confidence: 99%